2007
DOI: 10.1136/bjsm.2006.033316
|View full text |Cite
|
Sign up to set email alerts
|

Rule change incidence on physiological characteristics of elite basketball players: a 10-year-period investigation

Abstract: While anthropometric characteristics remained constant during the last decade, the change in rule of 2000 may have contributed in modifying the physiological profile of basketball players, by generally increasing their level of fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
54
1
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 23 publications
9
54
1
15
Order By: Relevance
“…The first two studies analysed games played more recently (2004–2008) than the third one (2001–2002 season). In fact, it has been suggested that the evolution of the game strategies and the optimization of the training process in recent years could be potential reasons for increased physical and physiological demands in basketball games [31, 32]. More specifically, the increases in the physical capacities of the athletes could contribute to a more aggressive basketball defensive system that produces more steals as FB starting actions.…”
Section: Discussionmentioning
confidence: 99%
“…The first two studies analysed games played more recently (2004–2008) than the third one (2001–2002 season). In fact, it has been suggested that the evolution of the game strategies and the optimization of the training process in recent years could be potential reasons for increased physical and physiological demands in basketball games [31, 32]. More specifically, the increases in the physical capacities of the athletes could contribute to a more aggressive basketball defensive system that produces more steals as FB starting actions.…”
Section: Discussionmentioning
confidence: 99%
“…Guards are in the main the shortest and fastest players in the team with the best ball control, while the centers are the tallest and the slowest players on the team. Recent studies that have investigated the differences between the players who play in different team positions have shown that the centers were taller and heavier, and had a higher body fat percentage (Jelicic et al, 2002;Sallet et al, 2005;Ostojic et al, 2006;Ben Abdelkrim et al, 2010) than the guards and forwards, but the guards had better aerobic and anaerobic capacities (Latin et al, 1994;Sallet et al;Ostojic et al;Cormery et al, 2008;Ben Abdelkrim et al, 2010), speed and agility (Ben Abdelkrim et al, 2010;Tsitskaris et al, 2003), while the forwards and centers were better in muscular strength and absolute power (Ben Abdelkrim et al, 2010;Ostojic et al).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently typical values of power, oxygen uptake, ventilation and heart rate could be observed using standardized exercise tests for perimeter and post players. The typical values of main cardiorespiratory indices in basketball were described, analysed and compared in respect to age, gender, level of performance, modification of rules and other external factors (Apostolidis et al, 2004; Laplaud et al, 2004; Gocentas et al, 2005; Sallet et al, 2005; Cormery et al, 2008; Castagna et al, 2009; Metaxas et al, 2009; Narazaki et al, 2009; Ziv et al, 2009). Despite the increased popularity of basketball a number of physiological investigations of the players are inadequate.…”
Section: Introductionmentioning
confidence: 99%